PRESENTEEISM – A NECESSARY DISCUSSION FOR HEALTH PROFESSIONALS - Santos Landim, Fernanda; Scremin, Marlete; Fernandes do Prado, Patrícia; Curty Ribeiro Christoff Ornelas, Yanca; Isabel Veloso Fonseca Antunes, Veronica; Costa Santos, Alessandra; Patrícia Fonseca Alves, Ellen; Katielle Pereira Silva, Raiane; Dayane Guimarães Fonseca, Adelia; Nascimento Arcanjo, Izabella; Geovanna Santos Leopoldo, Anielly; Silva Borges, Jhulie; et al. (Health and Society, 2026)
This study aims to understand presenteeism in connection with healthcare professionals. A theoretical-reflective study was conducted based on the concepts of health education and health promotion. The results show that working without full physical or mental health is not an isolated event, but a reflection of an organizational structure that prioritizes immediate productivity over the mental health of professionals. To mitigate this scenario, it is imperative that health management shift from a punitive view of absenteeism to a comprehensive view of worker health. This requires the implementation of policies that include proper team sizing, strengthening occupational health programs, and promoting an organizational culture that values self-care as a prerequisite for care safety.